Los juegos tradicionales para mejorar el estado emocional de los estudiantes del décimo año de educación básica, paralelo 'A', de la Unidad Educativa Babahoyo del cantón Babahoyo, Provincia Los Ríos. - Fajardo Junco, Luis Enrique (2025)
The present research, titled "TRADITIONAL GAMES TO IMPROVE THE EMOTIONAL STATE OF STUDENTS IN THE TENTH YEAR OF BASIC EDUCATION, PARALLEL 'A', OF THE BABAHOYO EDUCATIONAL UNIT OF THE BABAHOYO CANTON, LOS RÍNOS PROVINCE", aims to develop a teaching guide for the practice of traditional games within physical education classes. This research focuses on providing an educational tool that allows teachers to incorporate traditional games into their lessons, in order to improve the emotional well-being of students. Traditional games are important for the emotional state of tenth grade students because they offer multiple benefits that go beyond simple entertainment. Firstly, they provide an opportunity to release stress and anxiety accumulated during academic activities, allowing students to relax and enjoy moments of leisure. In addition, these games promote socialization and teamwork, which strengthens the bonds of friendship and the sense of belonging among classmates, key elements for a positive school environment. By participating in traditional games, students also develop important social skills such as empathy, cooperation, and effective communication. Likewise, these games help improve self-esteem and self-confidence, since students can experience achievements and learning in a playful and safe environment. To meet the research objectives, quantitative and qualitative methods were used with a descriptive approach, related to the context of the research and the reality of the students. An intentional sample of students was selected for data collection. After applying surveys and interviews, the emotional state of the students in relation to traditional games and their impact on the development of motor skills and physical abilities was evaluated.